The Hubungan Kemahiran Membaca Kritis dengan Kemahiran Menulis Teks Berita Siswa Kelas VIII Sekolah Menengah Pertama Negeri 7 Tanjungpinang Tahun Pelajaran 2022/2023 - Yurlina Dewi Siregar; Abdul Malik; Legi Elfitra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This study aims to see the relationship between critical reading skills and the ability to write news texts for Grade VIII students of Tanjungpinang 7 Public Middle School in the 2022/2023 academic year. This research method uses a quantitative approach with correlational research techniques. Data collection techniques using multiple choice objective tests and performance. The location of this research is in Tanjungpinang. The population in this study amounted to 448 students and the sample in this study amounted to 46 students. The results of the study: 1) from testing the data it was obtained that the students' critical reading proficiency had an average score of 64.97 with a total of 2989 with sufficient qualifications. 2) and proficiency in writing news texts has an average value of 81.34 with a total of 3742 good qualifications. 3) so, it can be concluded that there is a relationship between critical reading skills and the ability to write news texts for class VIII students of Tanjungpinang 7 Public Middle School in the Academic Year 2022/2023 with a result of 0.444 and the correlation value is in the interval 0.40-0.599 with the strength of the correlation relationship currently.